Itu Penerapan Model Pembelajaran Fisika Berbasis PjBL (Project Based Learning) untuk Meningkatkan Keterampilan Kolaborasi dan Kemampuan Berpikir Kreatif Peserta Didik pada Materi Fluida Kelas XI SMAN 1 Kampar Timur - Neneng Yanti; M. Rahmad; Azhar (Postgraduate, University of Mataram, 2023)
This study aims to determine the implementation of learning using the Project Based Learning model in each cycle to improve collaboration skills and creative thinking skills of SMAN 1 Kampar Timur class XI students in Physics learning. This research can contribute in the form of additional discourse to enrich knowledge in the field of education, especially in the development of science learning and can be a reference and alternative for teachers in the use of learning models, so that physics learning activities become more innovative and can stimulate students' creative thinking, so that there is an increase in the efficiency and effectiveness of physics learning activities, especially in fluid materials. Data collection techniques in this study are using observation and test methods. Based on the results of research that has been conducted, it can be concluded that the use of the project based learning (PjBL) model has a significant influence on students' collaboration skills and creative thinking abilities. Improved Collaboration Skills Students in the first cycle of the first meeting got an average score of 63.03 in the poor category, in the second meeting got an average score of 65.00 in the poor category, in the third meeting got an average score of 70.45 in the good enough category, and in the fourth meeting got an average score of 70.83 in the good enough category. In Cycle II the first meeting got an average score of 82.19 in the good category, in the second meeting got an average score of 83.48 in the good category, and in the third meeting got an average score of 86.59 in the good category. The ability to think creatively of students also increases in each cycle. In cycle I got an average score of 80.42 in the creative category and in cycle II got an average score of 83.12 in the very creative category.